Dinamika Tradisi Bόwό: Dampak Mahar pada Keharmonisan Keluarga Kristen di Suku Nias - Amoli Ndraha; Tedi Putra Damai Ndraha; Johanes P. Siregar; Ridwan Bangun; Lisdiaken Jenister Simangunsong (Vox Dei: Jurnal Teologi dan Pastoral, 2024)
The tradition of Bόwό is one of the important cultural practices in the Nias tribal society, where the prospective husband gives a certain amount of money or property to the family of the prospective wife as a dowry. This study aims to analyze the impact of the Bόwό tradition on Christian family harmony with a qualitative approach. Data were collected through in-depth interviews with members of the Nias Tribe who have been involved in this tradition, as well as analysis of related literature. The results of the study show that although Bόwό is considered a symbol of appreciation and seriousness of the prospective husband, this tradition also has the potential to cause conflict in the family. Social pressure, unrealistic expectations, and shifting cultural values are the main factors that affect the negative impact of this tradition on household harmony. This research provides in-depth insight into the local cultural dynamics of the Nias Tribe and suggests the need for a more flexible approach in preserving traditions without sacrificing family harmony.